Does Part-Time Faculty's Self-Efficacy Predict Critical Dimensions of Online College Teaching?. Issue 2 (3rd April 2017) - Hardy, Pamela; Shepard, Melvin; Pilotti, Maura
ABSTRACT: Surveys have repeatedly depicted a dismal picture of part-time teaching in academia, including low pay, scant benefits, limited institutional support, and lack of job security. Thus, the main purpose of the present study was to delve deeper into part-time faculty's ability to sustain the demands of a tough work environment by examining the extent to which specific psychological characteristics predict key self-reported dimensions of teaching in such faculty. The sample selected comprised part-time online instructors, as they are a relatively new and growing entity in academia. Teaching dimensions upon which faculty rated themselves belonged to three categories of factors known to shape satisfaction of faculty in the online environment (i.e., instructor-related, student-related, and institution-related). They included current satisfaction with the teaching profession, preparation to teach subject matter, responsibility for students' academic success, beliefs in the impact of one's teaching on student learning, perceived institutional support, and desire to remain in the teaching profession (i.e., commitment). Psychological characteristics examined were self-efficacy and self-monitoring. In this study, each key dimension of teaching was found to be positively related to one or more self-efficacy measures, whereas no links with self-monitoring were uncovered. The findings involving self-efficacy confirm those of studies of full-time faculty in that beliefs of one's capability are a source of resilience and, as such, a staple of the teaching profession.